Determinants of government efficiency - Hauner, David (IMF [Washington]US, 2008)
Compiles a cross-country panel dataset of government efficiency, encompassing 114 countries on all income levels from 1980 to 2006, with about 1,800 country-year observations for education and about 900 observations for health. Concludes that higher expenditure relative to GDP tend to be associated with lower efficiency.